Elegia jako gatunek filmowy. Adaptacja — inspiracja — sugestia - Koschany, Rafał (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
The question that this is article is concerned to answer is how the position of the film elegy can be best formally established — with its artistic representations, as well as its functioning in the genology of the genre. An attempt to provide definitive answers that emerge from interdisciplinary, film and literary discourse brings a number of substantial threads. Firstly, there is, indeed, no theoretical description of the elegy as a film genre, though the very name does appear in many titles. Secondly, it seems that a juxtaposition of available examples of film ad-aptations of elegies does not lead to any consistent conclusion, since, apart from the suggestion proposed by the author, they are different in terms of formal and thematic elements involved. Thirdly, any attempt at a genological profiling has to, somehow, refer to a more or less fixed literary genre and the relevant theory behind it. In a most general way, one can state, albeit with a number of reservations, that the elegiac film is characterized by a distinguishable style, often simply called the elegiac style, and the theme, very broadly associated with time and the theme of passing.